Evolution of Design Thinking and its use in Public and Private Organizations in Iceland - Pétursdóttir, Ingibjörg Rafnar; Torfason, Magnús Þór (Tímarit um viðskipti og efnahagsmál, 2019)
In recent years, design thinking methods have increasingly been used in development projects, both in the public and private sectors. This study explores how design thinking is used in different contexts within Icelandic administration and corporations. Qualitative interviews suggest that design thinking is seen as an empowering methodology that supports the conversation between different stakeholders, and that it is effective at managing the inherent uncertainty of innovative projects. On the other hand, the correspondents sense a certain tension between how different people approach design thinking. The authors theorize that this tension may in part originate in the history of design thinking, which has evolved through three distinct waves. The first wave is characterized by a close relationship with design methods and industrial design. The second wave is denoted by an emphasis on innovation and introduction of formal processes in design thinking. In the third wave, sustainability and the sustainable advantage of nations is in the foreground, with an increasing emphasis on the use of design thinking in public administration. The main themes uncovered in the interviews reflect these waves to some extent, and the theoretical approach suggested here may help understand different perspectives towards design thinking, both in Iceland and internationally. The results are important in light of the growing importance of design methods and because international organizations such as the European Union increasingly emphasize the use of design and design thinking. Á síðustu árum hefur færst í vöxt að beitt sé aðferðafræði sem kennd er við hönnunarhugsun (e. design thinking) í þróunarverkefnum, bæði á vegum hins opinbera og í einkageiranum. Í þessari grein er kannað hvernig hönnunarhugsun er beitt við mismunandi aðstæður innan íslenskrar stjórnsýslu og fyrirtækja. Fram kemur í viðtölum að hönnunarhugsun er talin styðja við samtal milli mismunandi hagsmunaaðila og valdeflingu þeirra, auk þess sem viðmælendur telja ...